DENOTATION AND CONNOTATION ON KEMENDIKBUD’S PUBLIC SERVICE AD ON PANDEMIC COVID-19 - Autumn Windy Alwasilah (Ma'soem University, 2021)
This paper analyzes a televised public service ad by Kemendikbud on their advice for the public to stay at home during the pandemic Covid-19 especially on the Eid day to stop the spread of the corona virus. The paper focuses on the four sign systems of the ad: photographs, written language, spoken language (narration), and moving images (McIlwain, 2007). Descriptive qualitative was employed in the paper to collect and analyze the data. This method was used because it provides an intensive, holistic description and analysis of a single entity. The analysis shows that the first-order and second-order signification by Barthes (1967) can be used in analyzing the four sign systems. Bold signs such as photographs, written and spoken language, and moving images in the ad that can be seen by viewers are denotations. Meanwhile, connotations represent the communication that occurs when signs meet with the user's emotions.